Follicular lesions with papillary nuclear characteristics: Differences in chromatin detected by computerized image analysis - Coelho, Bárbara Parente [UNESP]; Valentim, Flávia de Oliveira [UNESP]; Miot, Hélio Amante [UNESP]; Jaune, Danilo Takeshi Abe [UNESP]; Hayashi, Caroline Yuki [UNESP]; de Oliveira, Cristiano Claudino [UNESP]; Marques, Mariângela de Alencar [UNESP]; Tagliarini, José Vicente [UNESP]; Castilho, Emanuel Celice [UNESP]; Soares, Paula; Mazeto, Gláucia Maria Ferreira da Silva [UNESP] (Archives of Endocrinology and Metabolism, 2020)
Objective: Follicular lesions of the thyroid with papillary carcinoma nuclear characteristics are classified as infiltrative follicular variant of papillary thyroid carcinoma-FVPTC (IFVPTC), encapsulated/ well demarcated FVPTC with tumour capsular invasion (IEFVPTC), and the newly described category “non-invasive follicular thyroid neoplasm with papillary-like nuclear features” (NIFTP) formerly known as non-invasive encapsulated FVPTC.This study evaluated whether computerized image analysis can detect nuclear differences between these three tumour subtypes. Materials and methods: Slides with histological material from 15 cases of NIFTP and 33 cases of FVPTC subtypes (22 IEFVPTC, and 11 IFVPTC) were analyzed using the Image J image processing program.Tumour cells were compared for both nuclear morphometry and chromatin textural characteristics. Results: Nuclei from NIFTP and IFVPTC tumours differed in terms of chromatin textural features (grey intensity): mean (92.37 ± 21.01 vs 72.99 ± 14.73, p = 0.02), median (84.93 ± 21.17 vs 65.18 ± 17.08, p = 0.02), standard deviation (47.77 ± 9.55 vs 39.39 ± 7.18; p = 0.02), and coefficient of variation of standard deviation (19.96 ± 4.01 vs 24.75 ± 3.31; p = 0.003). No differences were found in relation to IEFVPTC. Conclusion: Computerized image analysis revealed differences in nuclear texture between NIFTP and IFVPTC, but not for IEFVPTC.
Keywords: Carcinoma, Papillary, Follicular; Cell nucleus; Histology; Thyroid neoplasms